ANALISIS PENGARUH PROFITABILITAS, UMUR PERUSAHAAN, UKURAN PERUSAHAAN, STRUKTUR KEPEMILIKAN DAN KUALITAS AUDITOR TERHADAP KETEPATAN WAKTU PELAPORAN KEUANGAN PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2020 - Sri Cindy Amalia; Alfurkaniati; Burhanuddin (UIR Press, 2023)
This study attempts to ascertain the impact of profitability, firm age, size, ownership structure, and auditor caliber on the timeliness of financial reporting in real estate and property companies listed on the IDX from 2018 to 2020.The population in this study were 62 Property and Real Estate companies listed on the IDX from 2018 to 2020. The research sample used purposive sampling method. Based on the purposive sampling method, the sample used was 40 companies for 3 years. So that the number of samples used was 120 samples. Data analysis using logistic regression using SPSS version 23. Based on the test results using logistic regression, it can be seen that the variables of profitability and auditor quality have no effect on the timeliness of financial reporting. Meanwhile, the variables of company age, company size and ownership structure affect the timeliness of financial reporting.